Unlocking the sustainable livelihoods strategy for forest communities in the southern slope of Mount Slamet, Indonesia - Budiyoko, Budiyoko; Zulkifli, Lutfi; Dharmawan, Budi; Sunendar, Sunendar; Rachmah, Malinda Aptika; Prasetyo, Kunandar; Saputro, Wahyu Adhi; Utami, Dewanti Risa (Sustainability in Debate, 2024)
Mount Slamet in Central Java Province, Indonesia, boasts significant biodiversity potential, yet communities on its southern slope grapple with poverty. This study delves into sustainable livelihood strategies for these communities. Employing participatory rural appraisal methods engages residents in identifying issues and devising solutions. Findings advocate for agrosilvopasture as a viable livelihood, blending crop farming, silviculture, and animal husbandry to balance environmental preservation with economic advancement. Additionally, the study underscores the importance of capacity-building within local communities, emphasizing skill and knowledge enhancement. By advocating community engagement and offering multifaceted sustainable livelihood strategies, this research enriches the discourse on sustainable development for forest communities residing on the southern slope of Mount Slamet.